Pharmacist Remote Review of Medication Prescriptions for Appropriateness in Pediatric Intensive Care Unit - Lazaryan, Moran; Abu-Kishk, Ibrahim; Rosenfeld-Yehoshua, Noa; Berkovitch, Sofia; Toledano, Michal; Reshef, Iris; Kanari, Tal; Ziv-Baran, Tomer; Berkovitch, Matitiahu (Frontiers in Pharmacology, 2016)
Background: One aspect of ordering and prescribing medication is the requirement for a trained professional to review medication orders or prescriptions for appropriateness. In practice, this review process is usually performed by a clinical pharmacist. However, in many medical centers there is a shortage of staff and a pharmacist is not always available. Objective: To determine whether remote review of medication orders by a pharmacist is a plausible method in a pediatric intensive care unit (PICU). Methods: A pharmacist from the pharmacy department reviewed medication orders of patients admitted to our PICU over a 7-month period for appropriateness. A special form for medical orders was filled in and sent to the physician in the PICU, who replied informing whether the recommendation had been accepted. The time spent by the pharmacist for this activity was recorded. Results: The review time for one medical record was 8.9 (95% CI, 6.9-10.9) minutes. Every additional drug prescribed increased the total review time by 0.8 (95% CI, 0.45-1.11) minutes. The pharmacist filled in 186 forms on 117 admissions for 109 children. The median review time was 15 (12.8-18.8) and 12 (9-15) minutes, respectively, for patients with psychiatric-neurologic disorders compared to those without (p=0.032). Usually, a daily workload of 240 minutes was needed for the pharmacist accompanying the round in contrast to 108 minutes per day needed to review all the medical records in 95% of the cases. The physician accepted 51.2%, rejected 11.9% and made no comment on 36.9% of the recommendations. Conclusion: Hospitals facing budget shortages can carry out focused remote reviews of prescriptions by the pharmacist.